Novel role of NLRP3-inflammasome in regulation of lipogenesis in fasting-induced hepatic steatosis - Liu B (Dove Medical Press, 2019)
Baoqing Liu,1 Xiaoxiang Mao,2,3 Dandan Huang,2,3 Fei Li,1 Nianguo Dong11Department of Cardiovascular Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Clinic Center of Human Gene Research, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaBackground: The liver coordinates a series of metabolic adaptations to maintain the energy balance of the system and provide adequate nutrients to key organs, tissues and cells during starvation. However, the mediators and underlying molecular mechanisms that mediate these fasting-induced adaptive responses remain unclear.Materials and methods: Male wild-type C57BL/6J littermates (8-weeks-old) were intraperitoneally injected with MCC950 or vehicle, and then randomly divided into three groups: fed, fasted, and refed. Plasma IL1β and insulin levels were detected by ELISA kits. Plasma and hepatic metabolites were determined using commercial assay kits. HepaRG cell line was applied to verify the regulation of NLRP3 on lipogenesis.Results: NOD-like receptor protein 3 (NLRP3) and its downstream inflammatory cytokines were significantly suppressed after 24 h fasting and recovered upon 6 h refeeding in plasma and liver tissues of mice. Moreover, fasting-induced hepatic steatosis and accompanied liver injury were ameliorated when mice were intraperitoneally injected with MCC950 (a selective NLRP3 inhibitor). Further study revealed that MCC950 suppressed sterol regulatory element-binding protein-1c (SREBP-1c) expression and transcriptional activity, thus inhibited lipogenesis in the liver, which may explain its role in stabilizing lipid metabolism.Conclusion: The NLRP3 inhibitor-MCC950 protects against fasting-induced hepatic steatosis. The novel and critical role of NLRP3 in lipogenesis may explain its importance in regulating the adaptive responses of the liver upon starvation stress and may provide therapeutic value.Keywords: metabolic homeostasis, starvation stress, NLRP3, MCC950, SREBP-1c